The Influence of Leadership Style on Employee Performance PT. Pos Indonesia - Cahyono, Arif (Yayasan Gema Bina Nusantara, 2024)
This research aims to find out how leadership style influences employee performance. In this research, the method used is the causality study method. The type of research used is descriptive. The nature of this research is quantitative. The population studied is all employees. The sampling method is probability sampling using simple random sampling techniques. The sample size is 100 employees. data collection using observation, interviews, and questionnaires. The results of processing the collected data will be tested using path analysis. Based on the research results, it was found that transactional and transformational leadership styles have a positive influence on employee performance. The analysis' findings demonstrate that respondents rate the transactional leadership style as good, with the manager issuing warnings to subordinates receiving the highest rating, while issuing sanctions receives a lower rating but is still in the good category. Meanwhile, the transformational leadership style was also rated as good, with definite goals as the highest aspect and the manager's ability to foster self-confidence in subordinates as the lowest aspect but still in the good category. Apart from that, employee performance is also considered good, with the employee's ability to maximize the use of company resources, increase work productivity, and contribute to teamwork being the highest aspects. However, the employee's ability to complete a number of jobs quickly has the lowest score, although it is still in the good category.